2019
DOI: 10.1155/2019/9426368
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Orthotopic Liver Transplantation-Induced Acute Gut Injury via α2-Adrenergic Receptor-Dependent Suppression of Oxidative Stress

Abstract: Patients with orthotopic liver transplantation (OLT) frequently develop acute gut injury (AGI), and dexmedetomidine (Dex) has been reported to exert a protective effect against AGI. We investigated whether Dex protects against AGI through antioxidative stress effects by the Nrf2/HO-1 antioxidative signaling pathway. Rats were randomly allocated into a sham group and six orthotopic autologous liver transplantation (OALT) groups receiving different doses of Dex together with/without α2-adrenergic receptor (AR) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Thus, we hypothesized that Dex could raise the expression of miR-146a and therefore downregulate the ERS and then oxidative stress, leading to the upregulation of cell viability and downregulation of cell apoptosis. It has been reported that Dex attenuates orthotopic liver transplantation-induced acute gut injury via α2-adrenergic receptor-dependent suppression of oxidative stress [36]. Yohimbine, an α2-adrenergic receptor antagonist, abolished the protection effect of Dex on regional I/R injury in the rat heart [37].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we hypothesized that Dex could raise the expression of miR-146a and therefore downregulate the ERS and then oxidative stress, leading to the upregulation of cell viability and downregulation of cell apoptosis. It has been reported that Dex attenuates orthotopic liver transplantation-induced acute gut injury via α2-adrenergic receptor-dependent suppression of oxidative stress [36]. Yohimbine, an α2-adrenergic receptor antagonist, abolished the protection effect of Dex on regional I/R injury in the rat heart [37].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, the intestinal injury model of autologous orthotopic liver transplantation in SD rats was established with reference to literature 12 . The anhepatic phase was 30 ± 1 min, and data were collected for 2 time points after reperfusion: 6 h and 24 h. The results showed that compared with that of rats in the sham group, the intestinal mucosal structure of the rats in the I/R group was damaged; Chiu's score, W/D, serum MDA, serum IL-6, and www.nature.com/scientificreports/ intestinal MDA, DAO, Fe 2+ levels were higher; and intestinal SOD, GSH and GPX4 levels were lower.…”
Section: Discussionmentioning
confidence: 99%
“…This study refers to the literature for the establishment of an I/R-induced intestinal injury model after autologous orthotopic LT in SD rats [12][13][14] . Before modeling, rats were fasted for 8 h and were allowed to drink water freely.…”
Section: Model Establishmentmentioning
confidence: 99%
“…Under electron microscope, the intestinal mucosa of LT rats presented evidence of derangement, manifested by intestinal villus epithelial cell necrosis, loss of ultrastructure, shortened mucosal villi length, increased gap between epithelial cells, accompanied by capillary congestion, interstitial edema, and inflammatory cell infiltration [ 30 ]. Widened space between intestinal epithelial cells observed in microscopic studies, which functionally means an opened paracellular route for translocation of luminal endotoxin and microbes, was shown to be based on reduced expression of the TJ proteins occludin and ZO-1 [ 40 ]. Intestinal epithelial cell injury has been further demonstrated by increased levels of several biomarkers in serum, including diamine oxidase, intestinal-fatty acid binding protein 2 (I-FABP-2), and d-lactate [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Widened space between intestinal epithelial cells observed in microscopic studies, which functionally means an opened paracellular route for translocation of luminal endotoxin and microbes, was shown to be based on reduced expression of the TJ proteins occludin and ZO-1 [ 40 ]. Intestinal epithelial cell injury has been further demonstrated by increased levels of several biomarkers in serum, including diamine oxidase, intestinal-fatty acid binding protein 2 (I-FABP-2), and d-lactate [ 40 ]. Moreover, enterocytes’ apoptosis is induced through activation of the toll-like receptor 4 (TLR4) / nuclear factor kappa B (NF-κB) signaling pathway, which leads to overexpression of proinflammatory cytokines like tumor necrosis factor alpha (TNF-α) and interleukin (IL)-1 β in the intestinal mucosa [ 30 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%